The studies on complex formation of metal borides in the reaction system of epoxidation of 1-octene with tert-butyl hydroperoxide by IR spectroscopy - Makota, Oksana; Trach, Yuriy (Publishing House of Lviv Polytechnic National University, 2007)
Вивчено комплексоутворення боридів молібдену і ванадію в реакційній системі епоксидування октену-1 гідропероксидом трет-бутилу методом інфрачервоної спектроскопії. Показано, що октен-1 утворює комплекс з металевою складовою у випадку бориду молібдену і з боридною складовою у випадку бориду ванадію.The complex formation of molybdenum and vanadium borides in the reaction system of 1-octene epoxidation with tert -butyl hydroperoxide by infrared spectroscopic analysis was studied. It was shown that 1-octene forms complex with metal moiety in the case of molybdenum boride and with boron moiety in the case of vanadium boride.
Вивчення комплексоутворення боридів металів у реакційній системі епоксидування октену-1гідропероксидом третбутилу методом ІЧ спектроскопії
Keywords: інфрачервона спектроскопія; каталізатор; епоксидування; олефін; гідропероксид; infrared spectroscopy catalyst; epoxidation; olefin; hydroperoxide